A study of positive accounting practice - Hisar Pangaribuan; Jenny Sihombing; Wing Wahyu Winarno; Denok Sunarsi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Financial accounting, as a branch of science from social science, practically describes the behavior of the presenters of financial statements. This study is confirmatory descriptive research, data obtained from the annual reports of banking companies on the Indonesia Stock Exchange. This study constructs a research model using four variables: accounting conservatism, managerial ownership, debt covenants, and political costs. The data is processed using path analysis, and the test is carried out through two stages: testing the direct and indirect effects. The direct effect finding proved that the bonus plan, debt covenant, and political cost hypothesis had been significantly practiced. Another direct influence finding also proved that managerial ownership has a significant effect on debt covenants and that political costs have a significant effect on debt covenants. This research also demonstrated that debt covenants could not mitigate the impact of political costs and managerial ownership on accounting conservatism practice. The board of commissioners, as the highest supervisory body and the supervisory units, has the responsibility to control the opportunistic behavior of managers so that banks can effectively practice a healthy financial statements process and so that public trust in banks increases.